A general approach to recovering market expectations from futures prices with an application to crude oil - Christiane Baumeister; Lutz Kilian (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
Futures markets are a potentially valuable source of information about market expectations. Exploiting this information has proved difficult in practice, because the presence of a timevarying risk premium often renders the futures price a poor measure of the market expectation of the price of the underlying asset. Even though the expectation in principle may be recovered by adjusting the futures price by the estimated risk premium, a common problem in applied work is that there are as many measures of market expectations as there are estimates of the risk premium. We propose a general solution to this problem that allows us to uniquely pin down the best possible estimate of the market expectation for any set of risk premium estimates. We illustrate this approach by solving the long-standing problem of how to recover the market expectation of the price of crude oil. We provide a new measure of oil price expectations that is considerably more accurate than the alternatives and more economically plausible. We discuss implications of our analysis for the estimation of economic models of energy-intensive durables, for the debate on speculation in oil markets, and for oil price forecasting.
urn:nbn:de:hebis:30:3-349023
Keywords: C53; D84; G14; Q43; 330; Futures; risk premium; market expectation; model uncertainty; forecast; oil price